Dbu maʼi spyi don gyi mchan ʼgrel zab don rab gsal sgron me : annotations to the pedagogical exegesis of Mādhyamika philosophy of Paṇ-chen Bsod-nams-grags-pa, the basic textbook of Blo-gsal-gliṅ College of ʼBras-spuṅs Monastery - Blo-bzaṅ-rta-mgrin, 1867-1937 (Series 2 -- Tibet House Library ; no. 25., 1974)
Annotations to the Dbu ma'i spyi don zab don gsal ba'i sgron me by Paṇ-chen Bsod-nams-grags-pa, 1478-1554.